Central African Republic : Poverty Reduction Strategy Paper; First Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2009)
This Joint Staff Advisory Note reviews the first annual progress report (APR) on implementation of the Poverty Reduction Strategy (PRS) of the Central African Republic (CAR). The APR shows that overall, the CAR has made good progress in implementing its PRS in 2008, and the direction of its policies and programs seems appropriate. The authorities have started addressing the most critical binding constraints to poverty reduction and growth in key areas, including political reconciliation, infrastructure, the social sectors as well as governance.